2005
DOI: 10.1002/cncr.21007
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase I dose‐escalation study using three‐dimensional conformal radiotherapy in the treatment of inoperable nonsmall cell lung carcinoma

Abstract: BACKGROUNDThe objective of this study was to report the results of a Phase I dose‐escalation study using three‐dimensional conformal radiation therapy (3D‐CRT) for the treatment of patients with nonsmall cell lung carcinoma (NSCLC).METHODSBetween 1991 and 2003, 104 patients were enrolled for 3D‐CRT at Memorial Sloan‐Kettering Cancer Center. The median patient age was 69 years. Twenty‐eight percent of patients had Stage I–II NSCLC, 33% of patients had Stage IIIA NSCLC, 32% of patients had Stage IIIB NSCLC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(107 citation statements)
references
References 28 publications
1
105
0
1
Order By: Relevance
“…Several studies from the University of Michigan, the Radiation Oncology Therapy Group (RTOG), and Memorial Sloan-Kettering Cancer Center (MSKCC) have shown the value of dose escalation to doses as high as 102.9 Gy in controlling locoregional recurrences in NSCLC. [4][5][6][7] However, even in these studies it was difficult to meaningfully escalate dose in patients with large tumors. The value of dose escalation was demonstrated in a study from MSKCC where Rengan et al reviewed the treatment of stage III tumors with large (≥ 100cc) gross tumor volumes (GTV) using 3D-CRT and found that a 10 Gy increase in dose correlated to a 36.4% decrease in local failure rates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from the University of Michigan, the Radiation Oncology Therapy Group (RTOG), and Memorial Sloan-Kettering Cancer Center (MSKCC) have shown the value of dose escalation to doses as high as 102.9 Gy in controlling locoregional recurrences in NSCLC. [4][5][6][7] However, even in these studies it was difficult to meaningfully escalate dose in patients with large tumors. The value of dose escalation was demonstrated in a study from MSKCC where Rengan et al reviewed the treatment of stage III tumors with large (≥ 100cc) gross tumor volumes (GTV) using 3D-CRT and found that a 10 Gy increase in dose correlated to a 36.4% decrease in local failure rates.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically related models, such as tumor control probability (TCP) and normal tissue complication probability (NTCP), have been widely used for evaluating the quality of RT plans 20 , 21 , 22 . In particular, several studies addressed TCP models for an inhomogeneously irradiated tumor 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 patient with grade 5 toxicity was reported in those 3 studies combined. 26,27,37 However, those trials reported on patients with stage I, II, and III NSCLC; only 16% received induction chemotherapy, and no concurrent chemotherapy was allowed. However, the reported RTOG grade !3 late lung toxicity rate of 14% in DCs I, II, and III appeared to be acceptable.…”
Section: Discussionmentioning
confidence: 99%